Interview with Prof. Dr. Katalin Botos - Grébel, Szabolcs (Public Finance Quarterly, 2024)
Prof. Dr. Katalin Botos’ work and research over the decades has covered a very diverse range of subjects in economics, but her research on the banking sector and the financial system has been outstanding. In her professional career, she has held positions as Deputy Minister of Finance, Minister of Banking and President of the Banking Supervisory Authority. The title of the biography, published last year, provides an excellent model for economists.